Bare nominals and optimal inference - Cohen, Ariel (ZAS Papers in Linguistics, 2006)
In this paper I discuss four type of bare nominal, and note that, in some sense, all of them appear to imply stereotypicality. I consider an account in terms of Bidirectional Optimality Theory: unmarked (bare) forms give rise to unmarked (stereotypical) interpretations. However, it turns out that, while the form of bare numerals is unmarked, the interpretation sometimes is not. I suggest that the crucial notion is not unmarkedness, but optimal inference: unmarked forms give rise to interpretations that are best used for drawing inferences. I propose a revision of Bidirectional Optimality Theory to reflect this.